# math

24x^4-12x^3+48x^2/-4x=6x^3+3x^2+12x
check this for me.

1. 👍 0
2. 👎 0
3. 👁 73
1. -6x^3+3x^2-12x

A positive divided by a negative equals a negative.

1. 👍 0
2. 👎 0
posted by Jen

## Similar Questions

1. ### algebra

24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please

asked by Keaton on June 3, 2010
2. ### calculus

i need to find the derivative using chain rule: (x^2 + 2x - 6)^2 (1-x^3)^2 i got the answer from a site but the problem is i cannot get my work to match up with the answer, i don't know what im doing wrong. answer: 10x^9 + 36x^8

asked by eric on January 13, 2014
3. ### alg2 check?

solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x=42 x=42/48 or 7/8 what where the two mistakes made in the problem? I said the 46 going to 48 and subtracting the 6 from 48?

asked by tyneisha on July 18, 2013
4. ### Derivatives

What is the fourth derivative of f(x)= e^-x^2. I got f''(x)=-2e^-x^2 + 4x^2e^-x^2 i need some help on find f''''(x) You have f(x) = e-x2 then f'(x) = -2x*e-x2 = -2x*f(x) f"(x) = (4x2 - 2))e-x2 = f(x)*(4x2 - 2)) f"'(x)= f'(x)*(4x2

asked by 413 on October 24, 2006
5. ### algebra

24x^4-12x^3+48x^2/-4x=6x^3-3x^2-4x

asked by Michael J on June 4, 2010
6. ### alg

Which of the following is equivalent to the rational number [3x / 4x]? a) 6x / 8x b) 12x / 24x c) 48x / 56x d) 3x / 5x a

asked by sean on June 28, 2010
7. ### Algebra 1

Rewrite the polynomial in descending order in its simplest form. here is #1 12x^2 y^2 z^3+2+24x^2 I think it should be writen 12x^2y^2Z^3+24x^2+2 then there is also question #6 I need help with is it x+y+xy+3x+4x^2 I think it

asked by Nora on May 28, 2008
8. ### Algebra

Can someone help me with this please. Andrew factored the expression 20x^3-12x^2+8x as 4x(5x^2-12x^2+8x) but when melissa applied the distributive law and multiplied out 4x(5x^2-12x^2+8x)she got 20x^3-48x^3+32x thus Andrews

asked by Anonymous* on August 2, 2012
9. ### algebra2

1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators by multiplying by 12X 12X*(1/3) - 12X*(5/6) = 12X*(1/X) Clear the fractions. 4X - 10X = 12 -6X=12 multipy by -1 6X=-12 Divide both sides by 6 6X/6 = -12/6 X = -2

asked by maria on January 16, 2007
10. ### Algebra

Andrew factored the expression 20x^3-12x^2+8x as 4x (5x^2-12x^2+8x). But when Melissa applied the distributive law and multiplied out 4x (5x^2-12x^2+8x), she got 20x^3-48x^3+32x^2; thus, Andrewâ€™s solution does not appear to

asked by traci on June 29, 2011

More Similar Questions